Avaliação da persistência de alterações comportamentais e neuroquímicas no modelo de depressão induzida por corticosterona em ratos - Gusmão, Camilla Teixeira Pinheiro (2022)
Depression is a severe and recurrent mental disorder, with heterogeneous clinical manifestations and a complex etiology that combines clinical-epidemiological, cellular, and molecular factors. The association of synaptic plasticity disorders with the pathogenesis of depression has redirected treatments in the search for substances that oppose the cellular effects of stress and depression. The stress increases circulating levels of glucocorticoids and the administration of exogenous corticosterone can induce depressive-like symptoms in animals. In order to evaluate the mechanisms related to synaptic plasticity and the regulation of the Hypothalamus-Pituitary-Adrenal (HPA) axis in the model of corticosterone-induced depression, Winstar rats (n = 36) were treated with corticosterone (40mg/kg) for 21 days. On the 21st or 28th day of the protocol (21 days of corticosterone administration and 7 days of drug suspension), the animals were evaluated for behavioral aspects and then euthanized. Samples of the hippocampus and hypothalamus were collected for analysis. The animals treated with corticosterone showed a depressive phenotype and maintained it after discontinuation of the drug. A reduction in GRIN1 (NR1) expression was found in the hypothalamus and an increase in NMDA immunostaining in the hippocampus of animals treated with corticosterone. There was a reduction in the expression of DLG4 (PSD95) in the hypothalamus and of the PSD95 protein in the hippocampus of the treated animals. Such changes were not maintained after 7 days of drug discontinuation. NR3C2 (MR) expression was reduced in the hippocampus of corticosterone-treated animals and was restored after 7 days of drug withdrawal. Additionally, there was an increase in the expression of matrix metalloproteinase-2 in the hippocampus, which significantly reduced after 7 days of corticosterone suspension. Taken together these findings point to the weakening of synapses in the hippocampus and the hypothalamic structural rearrangement in the corticosterone model. Recovery in NR3C2 (MR) expression and reduction in MMP2 expression after cessation of corticosterone administration may represent an initial mechanism of reversal of depressive-like symptoms in this model.